Extreme inflation and time-varying consumption growth - Ilya Dergunov; Christoph Meinerding; Christian Schlag (Deutsche Bundesbank, 2019)
In a parsimonious regime switching model, expected consumption growth varies over time. Adding in ation as a conditioning variable, we uncover two states in which expected consumption growth is low, one with high and one with negative expected in ation. Embedded in a general equilibrium asset pricing model with learning, these dynamics replicate the observed time variation in stock return volatilities and stock-bond return correlations. Furthermore, they provide an alternative way to come up with a measure of time-varying disaster risk in the spirit of Wachter (2013). Our findings imply that both the disaster and the long-run risk paradigm can be extended towards explaining movements in the stock-bond return correlation.
Keywords: E31; E44; G12; 330; long-run risk; inflation; recursive utility; filtering; disaster risk